2022
DOI: 10.3389/fonc.2022.960269
|View full text |Cite
|
Sign up to set email alerts
|

Association between microRNA 671 polymorphisms and the susceptibility to soft tissue sarcomas in a Chinese population

Abstract: This study evaluated the association between the microRNA (miRNA) gene polymorphisms and the susceptibility to soft tissue sarcomas (STSs). In this case–control study, DNA was extracted from leukocytes in peripheral blood, which was collected from 169 STSs patients and 170 healthy controls. Three SNPs for miR-210, five SNPs for miR-206, two SNPs for miR-485, two SNPs for miR-34b, two SNPs for miR-671, and three SNPs for miR-381 were investigated and genotyped using a Sequenom Mass ARRAY matrix-assisted laser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Association between miR-671 variants and risk of soft tissue sarcomas has been assessed in a population of Chinese patients and healthy controls. The results of this study has shown association between miR-671 rs1870238 GC + CC and miR-671 rs2446065 CG + GG genotypes and risk of this type of tumor after adjustment for age and smoking ( Zhang et al, 2022a ).…”
Section: Cell Line Studiesmentioning
confidence: 72%
“…Association between miR-671 variants and risk of soft tissue sarcomas has been assessed in a population of Chinese patients and healthy controls. The results of this study has shown association between miR-671 rs1870238 GC + CC and miR-671 rs2446065 CG + GG genotypes and risk of this type of tumor after adjustment for age and smoking ( Zhang et al, 2022a ).…”
Section: Cell Line Studiesmentioning
confidence: 72%